Heeelllllloooooo! :D
Okay this is a very similar question to the one I answered earlier....
I'll show you step by step so you will be able to do this in the future on your own
(y - y₁) = m(x - x₁) -----> point-slope form
(y + 6) = (-0.38)(x - 5)
y + 6 = -0.38x + 1.9
<u>y = -0.38x - 4.1</u><u />
There you go!
<u>Please vote me for Brainliest if there is a second answer!!!</u> ^__^
Answer:
answer choice B.......Cell phones as an educational tool
Step-by-step explanation:
self explanatory
5(3)-(-3)
15- (-3)
15+3 = 18
Answer:
Step-by-step explanation:
25
5,000 divided by 200